Penerapan Pola Asuh Orang Tua Etnis Banjar Dalam Internalisasi Beribadah Pada Anak - Anisa nisa; Halimatusyadiyah Diyah; Eka Ambar Setia Putri Setia Putri; Sandra Putri Ananda; Marsella Nadia Putri; Fachrul Rozie (Nunchi : Islamic Parenting Journal, 2024)
This research employs a qualitative approach with a narrative type. The aim of this study is to explore the implementation of Banjarese ethnic parents' parenting patterns in internalizing worship behaviors in children. Children are considered as gifts from Allah SWT, requiring attention and guidance from parents. The family is regarded as the primary environment crucial in shaping children's characters. In educating children, good parenting patterns and two-way communication between parents and children are paramount. Parents should instill religious values from an early age, using approaches suitable for the child's age and understanding, and provide positive examples. Parenting patterns can be influenced by social and cultural factors as well as the living environment. The research also encompasses a study on the parenting patterns of Banjarese families in Samarinda, East Kalimantan, emphasizing religious education from an early age and the habituation of worship practices. Interview results with Banjarese families indicate that religious education starts as early as 2 years old in a gentle and supportive manner.